Nanocomposite flexible pressure sensor for biomedical applications - Sepúlveda, A. T. (2011)
A new approach for the fabrication of flexible pressure sensors based on aligned carbon nanotubes (A-CNTs) is described in this paper. The technology is suitable for blood pressure sensors that can be attached to a stent-graft and deployed during an endovascular aneurysm repair (EVAR) procedure. Given the specifications of EVAR, the device should be foldable (extremely flexible) and characterized by a (very small) profile that integrates with the stent-graft cross section. A-CNTs embedded in a flexible substrate of polydimethylsiloxane (PDMS), a transparent, nontoxic and biocompatible silicone elastomer, are used to fabricate elements of the capacitive sensors. Fabricated prototypes validate our approach and show that CNTs/PDMS layered composites can be used to create highly flexible pressure sensors.